Perbedaan profil lipid pada remaja obes dan tidak obes di Kecamatan Bolangitang Barat - Tandra, Hendry J.R.; Bodhi, Widhi; Kepel, Billy J. (Universitas Sam Ratulangi, 2016)
Abstract: Obesity might cause dyslipidemia, marked by increased cholesterol, triglycerides, and LDL levels, as well as reduced HDL level. Dyslipidemia is related to atherosclerosis that can result in cardiovascular diseases. This study was aimed to identify differences of lipid profiles in obese and non-obese teenagers at West Bolangitang, North Bolaang Mongondow. This was an observational analytical study with a cross sectional design conducted from October to November 2016. Subjects were 60 teenagers obtained by using consecutive sampling method and were divided into two groups: obese (29 teenagers) and non-obese (31 teenagers). Lipid profile examinations were performed on all of them. Statistical analysis of total cholesterol level of the two groups used independent t test (p=0.002) dan Pearson correlation test (p=0.028). The normality test of triglyseride level showed that data were not normally distributed, therefore, the analysis was continued with Mann-Whitney test (p=0.328) and Spearman correlation test (p=0.542). The normality test of LDL level showed that data were not normally distributed, therefore, the analysis was continued with Mann-Whitney test (p=0.004) and Spearman correlation test (p=0.032). The normality test of HDL level showed that data were not normally distributed, therefore, the analysis was continued with Mann-Whitney test (p=0.063) and Spearman correlation test (p=0.054). Conclusion: There were significant differences of total cholesterol and LDL levels but there were no significant differences of triglyceride and HDL levels between obese teenagers and non-obese teenagers.Keywords: lipid profile, adolescents, obesity.Â Abstrak: Obesitas dapat menyebabkan peningkatan lipid kolesterol, trigliserida, maupun LDL dan penurunan lipid HDL yang disebut dislipidemia. Dislipidemia berhubungan erat dengan terjadinya aterosklerosis yang dapat menimbulkan penyakit kardiovaskular. Penelitian ini bertujuan untuk mengetahui perbedaan profil lipid pada remaja obes dan remaja tidak obes di Kecamatan Bolangitang Barat, Kabupaten Bolaang Mongondow Utara. Jenis penelitian ialah observasional analitik dengan desain potong lintang. Penelitian dilaksanakan pada bulan Oktober dan November 2016 dengan sampel penelitian berjumlah 60 remaja terdiri dari kelompok remaja obes (29 orang) dan kelompok remaja tidak obes (31 orang) yang diperoleh dengan metode consecutive sampling. Pemeriksaan profil lipid dilakukan pada semua remaja. Uji statistik terhadap kadar kolesterol total antara kedua kelompok menggunakan uji independent t test (p=0,002) dan uji Pearson correlation (p=0,028). Uji normalitas terhadap kadar trigliserida mendapatkan data tidak terdistribusi normal sehingga dilanjutkan dengan uji Mann-Whitney (p=0,328) dan uji korelasi Spearman (p=0,542). Uji normalitas terhadap kadar LDL mendapatkan data tidak terdistribusi normal sehingga dilanjutkan dengan uji Mann-Whitney (p=0,004) dan uji korelasi Spearman (p=0,032). Uji normalitas terhadap kadar HDL mendapatkan data tidak terdistribusi normal sehingga dilanjutkan dengan uji Mann-Whitney (p=0,063) dan uji korelasi Spearman (p=0,054). Simpulan: Terdapat perbedaan bermakna dalam hal kadar kolesterol total dan LDL, tetapi tidak terdapat perbedaan bermakna dalam hal kadar trigliserida dan HDL antara remaja obes dan tidak obes. Kata kunci: profil lipid, remaja, obesitas